منهج الشيخ أحمد ديدات في مناظراته: An Analysis of Shaikh Aḥmd Dīdāt Methodology in Religious Debate - Naqeebullah; Dr. Sajjad Ahmed (MEI, 2023)
Islam and Christianity are missionary religions, as both stand as the most popular religions around the globe and always tries to gain a greater degree of popularity. Both the religion play an important role in decision-making. If the relations between both religions are strained, then it has great influence on global politics. Indeed the issue of dialogue has become very essential in contemporary age in order to overcome the interreligious tensions. The world needs a strong debate among religions, especially between Christianity and Islam, to abolish the misunderstanding that exists in the minds of their followers. under these circumstances Al-šīẖ Aḥmd Dīdāt emerged as a key Muslim figure from Sʿūd Afrīqh Who not only engaged various Cristian (krīsǧn) missionaries in religious polemic but He also interacted with more than thirty top missionaries across the world. Since Aḥmd dīdāt,s goal was to always emerge victorious when debating and disputing with Christian missionaries, he saw to it that he familiarized himself with their texts and arguments. Accordingly, over the years, his knowledge about the Bible increased to such a degree that he could comfortably quote from any part of the text. This article will analyse the methodology of in religious Aḥmd Dīdāt polemic, which made him a global figure. As it will also highlight his methodologies before,during and after dialouge , and his rational approaches in debate.